Systemic Economic Offences as International Crimes : Theorising a New Paradigm of Mass Criminality - Citeroni, Nicole ; 0009-0003-6769-9565 (Studies in International Law, 2026)
This open access book asks whether international economic crime can qualify as an international crime and be prosecuted as such. Taking a four-part approach to the question, it traces the origins of the concept of international economic crime, and draws the line between ordinary economic crimes and economic offences of international significance. To this end, it examines six cases involving the commissions of serious economic crimes in different regions of the world, including Europe, the Americas and Africa: the crime of grand corruption in the Petrobras case; the theft of natural resources in the Niger Delta region and Liberia; the international money-laundering scheme in the Bolichicos case; the crime of financing terrorism in the Chiquita case; the Volkswagen conspiracy case in the US and the Haarde case related to gross-negligence in preventing serious economic damage. It then goes on to discuss a potential sui generis category of international economic crimes, before considering the advantages and the challenges of the multilevel enforcement system of international criminal justice in prosecuting such crimes. This book provides an innovative and original avenue for the analysis of a controversial and yet overlooked topic in international criminal law.